Stevens-Johnson Syndrome Caused by Enzalutamide: A Case Report and Literature Review - Deng, Min; Chai, Huirong; Yang, Meng; Wei, Xueman; Zhang, Wenjun; Wang, Xuebin; Li, Juanjuan; Wang, Zhuo; Chen, Haitao (Frontiers in Oncology, 2021)
Objective Enzalutamide is the most frequently prescribed compound for treating metastatic castration-resistant prostate cancer (mCRPC). Common adverse drug events of enzalutamide are febrile neutropenia, hot flashes, hypertension, and fatigue. Methods We present a case of a patient with mCRPC who received enzalutamide and developed Stevens-Johnson syndrome (SJS). The culprit drug was confirmed using the Naranjo Adverse Drug Reaction Probability Scale. Clinical characteristics and management principles were analyzed in combination with literature reports. Results SJS occurred within two weeks of enzalutamide therapy. Supportive care such as steroid treatment led to a complete resolution of skin lesions and improved clinical symptoms after three weeks. Conclusion Most cutaneous adverse events occur early during enzalutamide therapy, and close observation should be given within two weeks of starting treatment.